Thermodynamic and structural evolution of mechanically milled and swift heavy ion irradiated Er2Ti2O7 pyrochlore. (December 2019) - Chung, Cheng-Kai; O'Quinn, Eric C.; Neuefeind, Joerg C.; Fuentes, Antonio F.; Xu, Hongwu; Lang, Maik; Navrotsky, Alexandra
Abstract: Design and synthesis of thermodynamically metastable yet kinetically achievable materials possessing various desired functional and physical properties have recently drawn tremendous scientific-attention. In addition to conventional heat treatments and wet chemistry approaches, energy deposition into materials can induce unique nonequilibrium phases with distinct structures, chemistry, energetics, and properties. Mechanochemical synthesis and ion beam irradiation are two processing techniques that provide access to phases and states far from equilibrium. By a combination of high temperature oxide melt solution calorimetry, differential scanning calorimetry (DSC), neutron pair distribution function (PDF) analysis, and supplementary powder X-ray diffraction (XRD), the energetics and multiscale structural evolution on annealing of ball milled and swift heavy ion irradiated Er2 Ti2 O7 pyrochlore were investigated. Despite very similar structural modifications of local atomic arrangements and only minor differences in the long range structure, both types of damage yield significant difference in the energetics of the produced material. The energy of destabilization in the milled sample (70.2 ± 8.2 kJ/mol) is much less endothermic than that in the irradiated sample (457.3 ± 8.0 kJ/mol). The DSC profiles, supported by neutron scattering, X-ray diffraction, and solution calorimetry, reveal decoupled annealing events in different temperature ranges, separating crystallization of long range pyrochlore structure from annealing of short range weberite-like domains. Graphical abstract: Image, graphical abstract